D-lactic acid biosynthesis from biomass-derived sugars via Lactobacillus delbrueckii fermentation - Zhang, Yixing; Vadlani, Praveen V. (My University, 2014)
Poly-lactic acid (PLA) derived from renewable resources is considered to be a good substitute for petroleum-based plastics. The number of poly L-lactic acid applications is increased by the introduction of a stereocomplex PLA, which consists of both poly-L and D-lactic acid and has a higher melting temperature. To date, several studies have explored the production of L-lactic acid, but information on biosynthesis of D-lactic acid is limited. Pulp and corn stover are abundant, renewable lignocellulosic materials that can be hydrolyzed to sugars and used in biosynthesis of D-lactic acid. In our study, saccharification of pulp and corn stover was done by cellulase CTec2 and sugars generated from hydrolysis were converted to D-lactic acid by a homofermentative strain, L. delbrueckii, through a sequential hydrolysis and fermentation process (SHF) and a simultaneous saccharification and fermentation process (SSF). 36.3 g Lˉ¹ of D-lactic acid with 99.8 % optical purity was obtained in the batch fermentation of pulp and attained highest yield and productivity of 0.83 g gˉ¹ and 1.01 g Lˉ¹ hˉ¹, respectively. Luedeking–Piret model described the mixed growth-associated production of D-lactic acid with a maximum specific growth rate 0.2 hˉ¹ and product formation rate 0.026 hˉ¹, obtained for this strain. The efficient synthesis of D-lactic acid having high optical purity and melting point will lead to unique stereocomplex PLA with innovative applications in polymer industry.
Keywords: D-lactic acid; Fermentation; Corn stover; Pulp; Biosynthesis